Characteristics and long-term kinetics of an azobenzene derivative and a donor-acceptor Stenhouse adduct as orthogonal photoswitches - Schmitt, Tanja; Huck, Christian; Oberhof, Nils; Hsu, Li-Yun; Blasco, Eva; Dreuw, Andreas; Tegeder, Petra (Physical chemistry, chemical physics, 2024)
Light-triggered molecular switches are extensively researched for their applications in medicine, chemistry and material science and, if combined, particularly for their use in multifunctional smart materials, for which orthogonally, i.e. individually, addressable photoswitches are needed. In such a multifunctional mixture, the switching properties, efficiencies and the overall performance may be impaired by undesired mutual dependences of the photoswitches on each other. Within this study, we compare the performance of the pure photoswitches, namely an azobenzene derivative (Azo) and a donor-acceptor Stenhouse adduct (DASA), with the switching properties of their mixture using time-resolved temperature-dependent UV/VIS absorption spectroscopy, time-resolved IR absorption spectroscopy at room temperature and quantum mechanical calculations to determine effective cross sections, switching kinetics as well as activation energies of thermally induced steps. We find slightly improved effective cross sections, percentages of switched molecules and no increased activation barriers of the equimolar mixture compared to the single compounds. Thus, the studied mixture Azo + DASA is very promising for future applications in multifunctional smart materials.